Left ventricular dysfunction in patients with chronic obstructive pulmonary disease (COPD) - Mahat, Ravi; Nepal, Bipin; Panjwani, Ashok K. (Grande Medical Journal, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a common disease with a rising global incidence. It is recognized as a chronic inflammatory condition with multisystem involvement. Among its associated comorbidities, cardiovascular disease (CVD) is particularly significant, contributing to increased morbidity and mortality in COPD patients. The purpose of the study was to determine the prevalence of left ventricular (LV) dysfunction in stable COPD patients.MethodThis cross-sectional study was conducted at department of Chest Medicine, Jinnah Postgraduate Medical Centre, Karachi, Pakistan, enrolled 85 COPD patients aged 40-70 years with over six month's disease duration. Spirometry evaluated COPD severity; echocardiography assessed left ventricular dysfunction. Data were analyzed using SPSS-19 (descriptive statistics, chi-square; p≤0.05).ResultThe study included 85 COPD patients 61 (71.8%) were males and 24 (28.2 %) females. The mean age of the patients was 59.01 ±7.62 years. Mean duration of COPD was 7.17±5.58 years. Echocardiography revealed left ventricular (LV) systolic dysfunction in 12 patients (14.1%), showing  a significant association with advanced age (p = 0.01). LV diastolic dysfunction was identified in 33 patients (38.8%), with males exhibiting a higher prevalence compared to females (p = 0.033). Disease duration showed no significant correlation with LV dysfunction outcomes.ConclusionThe results show that LV dysfunction is quite common in COPD patients, and it is especially associated with advanced age, male gender, and the severity of the disease. Because early diagnosis of left ventricular dysfunction may enhance risk classification and treatment approaches, these findings highlight the significance of routine cardiovascular screening.